Lactococcus strains with psychobiotic properties improve cognitive and mood alterations in aged mice - Gao, Kan; Chen, Cailing; Zheng, Zhiyao; Fan, Qiuling; Wang, Haifeng; Li, Yanjun; Chen, Su (Frontiers in Nutrition, 2024)
Aging often accompanies cognitive and mood disturbances. Emerging evidence indicates that specific probiotics mitigate cognitive and mood dysfunctions. Strains within Lactococcus, a subgroup of probiotics, including L. lactis and L. cremoris are shown beneficial effects on brain functions via the gut microbiota-brain axis (GBA). Our previous study identified two Lactococcus strains (L. lactis WHH2078 and L. cremoris WHH2080) with the ability to promote the secretion of gut 5-hydroxytryptophan (5-HTP), the precursor of the GBA mediator 5-hydroxytryptamine (5-HT).In this study, the modulatory effects of WHH2078 and WHH2080 on cognitive and mood alternations were investigated in aged mice. Oral administration of WHH2078 and WHH2080 (1×10 9 CFU/mL/day) in aged mice (12-month-old) for 12 weeks significantly improved cognitive and depressive-and anxiety-like behaviors. The neuronal loss, the 5-HT metabolism dysfunction, and the neuroinflammation in the hippocampus of aged mice were restored by WHH2078 and WHH2080. the disturbances in the serum tryptophan metabolism in aged mice were unveiled by metabolomics, notably with decreased levels of 5-HT and 5-HTP, and increased levels of kynurenine, 3-hydroxykynurenine, and indolelactic acid, which were reversed by WHH2078 and WHH2080.Regarding the gut microbial community, WHH2078 and WHH2080 restored the increased abundance of Firmicutes, Desulfobacterota, and Deferribacterota and the decreased abundance of Bacteroidota and Actinobacteriota in aged mice. The beneficial effects of the two strains were linked to the modulation of 5-HT metabolism and gut microbiota. Our findings point to the potential role of Lactococcus strains with 5-HTP-promoting abilities as therapeutic approaches for agerelated cognitive and mood disorders.